The Emancipatory Potential of Aesthetic Experience: Rancière on Kant and Schiller - Ayas Onol, Tugba (Problemos, 2025)
This paper examines the emancipatory potential of aesthetic experience through a comparative reading of Immanuel Kant, Friedrich Schiller, and Jacques Rancière. It argues that Rancière both inherits and transforms the Kantian-Schillerian legacy by shifting the question of freedom from free accord of faculties or moral autonomy to a meaning-disruptive experience of equality. While Kant and Schiller conceptualize the disinterested experience of the spectator in aesthetic or ethical terms, Rancière interprets it as a condition that can trigger a struggle for equality. The article traces this entangled genealogy to demonstrate how Rancière’s notion of aesthetic experience cancels hierarchies and opens a space for dissensus, only within which politics can occur. By clarifying the conceptual transitions from Kant’s sensus communis to Schiller’s play drive and Rancière’s dissensual common sense, the paper demonstrates how, for Rancière, aesthetics is a field of disagreement, revealing aesthetic experience as a political act that disrupts the pre-established sensible orders; and how it generates equality through discord, transforming aesthetic contemplation into a mode of emancipation from the dominant orders of meaning and sense.